Pelatihan Pelaporan Keuangan Sederhana dan Manajemen Keuangan Bagi UMKM yang Terdaftar di Bank Wakaf Mikro UNISA - Rigel Nurul Fathah; Teti Anggita Safitri (LPPM Universitas Trunojoyo Madura, 2020)
A business both small and large scale requires good financial management. The potential of UMKM so far, has not been sufficiently exploited to the maximum, on the contrary many MSME actors (owners) actually often experience internal problems making it difficult to develop and compete both among MSMEs and with large producers. The problem of financial management is one of the problems that is often encountered in MSMEs. Financial management and financial management are important aspects for the progress of MSMEs. Financial management can be done through accounting. Accounting is a systematic process to produce financial information that can be used for decision making for its users.The proposed Community Service Program is to provide MSME financial training, specifically regarding standardized and simple financial management, along with the process of socialization and assistance to MSMEs and financial management. Centralized training conducted is training on simple financial management methods and MSME financial management. The output of this program is that MSME practitioners gain knowledge of simple financial reporting and financial management.